Modeling intentions to sanction among anglers in a catch-and-release recreational fishery for golden dorado (Salminus brasiliensis) in Salta, Argentina. Issue 4 (4th July 2018) - Chapman, Daniel A.; Gagne, Tyler O.; Ovitz, Kimberly L.; Griffin, Lucas P.; Danylchuk, Andy J.; Markowitz, Ezra M.
ABSTRACT: Catch-and-release (C&R) angling is a powerful tool for reducing impacts on recreationally targeted fishes. Although C&R can be mandated in fisheries through regulation, voluntary adoption and informal management are often critical due to minimal enforcement opportunities. Anglers themselves may play a role in increasing C&R adoption through interpersonal sanctioning (i.e., self-policing). To date, little research has examined factors that predict the willingness of anglers to sanction others' behavior. We present results from surveys ( n  = 49) with anglers in Argentina to explore their motivations to sanction other anglers within their stakeholder community. Anglers with the strongest intentions to sanction were younger and more open to adopting best practices, identified fishing as important to their lifestyle, and expressed high environmental concern relative to other anglers. Our findings highlight the role that recreational anglers can play in promoting best practices via interpersonal sanctioning and identify barriers that inhibit this type of action.